Interpersonal savvy : building and maintaining solid working relationships - Gentry, Bill (Report (Center for Creative Leadership) ;, 2013)
The success of your daily interactions with others, whether during formal meetings or encounters at the water cooler, can make or break your success in the workplace. Having interpersonal skills will allow you to motivate, inspire, and successfully lead others, as well as further your own career development.